A Simple Insight into Convolutional Neural Network Research Using VOSviewer, Python, and Gen-AI - Samsul Arifin; Ade Kurniawan; Muhammad Faisal; Merios Gusan Putra; Tiawan; Dani Lukman Hakim; Abdul Azis Abdillah; Wiwik Wiyanti (MBI, 2026)
This study presents a bibliometric analysis of research trends in Convolutional Neural Networks (CNN) published in 2023. Using the Scopus database, metadata for 2,185 journal articles was extracted based on criteria including open access status, English language, and classification under Computer Science. The research employed a systematic methodology involving data extraction, preprocessing, and network visualization. VOSviewer was used to map co-authorship networks, keyword co-occurrence, and citation patterns, while Python supported advanced data processing, topic modeling, and trend analysis. Keyword analysis highlighted the prominence of terms such as